Contract-based hierarchical resilience management for cyber-physical systems - Haque, Mohammad Shihabul (2020)
Cyber-physical systems satisfy user requirements through close collaboration among physical and cyber components. Software-based resilience management solutions can provide flexibility in dealing with component failures. To improve efficiency and ease of implementation, we present a contract-based hierarchical resilience management framework.